THE INFLUENCE OF BRAND IMAGE ON CONSUMER BUYING BEHAVIOR: AN AI-POWERED SENTIMENT ANALYSIS IN THE DIGITAL AGE - Riyani, Fajar (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This consider points to assess the affect of brand image on customer obtaining behavior in a computerized setting by joining quantitative strategies and counterfeit insights (AI)-based opinion examination. Essential information collection was conducted through an internet overview of 212 respondents matured 21–35 a long time who routinely make online buys, whereas auxiliary information was gotten from 5,000 customer comments on social media and e-commerce destinations. The comes about of the relapse examination appeared that brand image components such as believe (β = 0.37), seen quality (β = 0.31), and passionate association (β = 0.28) have a critical impact on buy purposeful (R² = 0.62, p < 0.01). The discoveries from the estimation investigation appeared that 72% of customer suppositions were positive, supporting the quantitative comes about and underlining the significance of the enthusiastic viewpoint in acquiring choices. This think about contributes to the advancement of hypothesis by combining essential and auxiliary information analyzed utilizing AI innovation, and emphasizing the significance of computerized notoriety and enthusiastic perspectives in forming brand quality. The comes about of this ponder open up unused points of view in creating data-based promoting procedures within the computerized period.